Dualisme Sistem Pewarisan Menurut Hukum Perdata dan Hukum Adat Muko-Muko - Lestari, Dewi; Jaya, Dwi Putra (Berasan: Journal of Islamic Civil Law, 2022)
Abstract: The purpose of this study is to answer the problem of the Dualism of the Inheritance System According to Civil Law and Mukomuko Customary Law. This research uses an empirical approach that aims to understand that the law is not solely a set of laws and regulations. Based on the results of research and discussion on the division of patrilinial inheritance, the author can conclude as follows: The people of mukomuko district still use the customary law system in the division of inheritance law so that the lack of knowledge of the community about civil law and society in general therefore the community is only guided by the family way related to the transfer of inheritance rights. The inheritance system according to civil law and customary law mukomuko Transfer of inheritance rights regarding the skills and acting authority of those who will transfer and accept the transfer of rights to the Inheritance. The obstacles that occur in the implementation of the transfer of property rights due to inheritance are caused by the community being reluctant to use the national legal system, namely civil law.